Fatty acid profile and estimated desaturase activities in whole blood are associated with metabolic health - Svendsen, Karianne (Lipids Health Dis, 2020)
BACKGROUND: The aim was to investigate if fatty acid profile and estimated desaturase activities; stearoyl CoA-desaturase (SCD), delta-5-desaturase and delta-6-desaturase (D5D; D6D), differ between individuals with metabolically healthy (MH) and unhealthy (MU) phenotypes. We also explored these associations according to BMI categories. METHODS: Men and women at moderately elevated risk of cardiovascular disease were included in this cross-sectional study (n = 321). If subjects met ≥4 out of 5 criteria (elevated triglycerides, total and LDL-cholesterol, HbA1c and low HDL-cholesterol), they were classified as MU (n = 52). If levels were within reference ranges for ≥3 of the same criteria, subjects were classified as MH (n = 150). Utilizing the entire population, a score ranging from 0 to 5 denoting the number of MU criteria met was computed. Estimated desaturase activities were calculated as product-to-precursor ratio of fatty acids in whole blood (SCD16 [16:1n7/16:0], SCD18 [18:1n9/18:0], D5D [18:3n6/18:2n6], D6D [20:4n6/20:3n6]). RESULTS: Individuals with MH had lower estimated SCD16 and SCD18 activities, whereas estimated D6D activity was higher compared to MU. Similar, SCD16 and SCD18 increased, whereas D6D decreased with increasing criteria of MU. Trends were similar across BMI categories. CONCLUSIONS: This study supports the notion of estimated desaturase activities as possible novel biomarkers of metabolic health irrespectively of BMI.